FLUCTUATIONS IN THE CLIMATE OF EUROPE OVER THE LAST THOUSAND YEARS - Zolotokrylin A.N.; Krenke A.N.; Fogel F.A. (My University, 1988)
In reconstructing the climate over long epochs, we make use of historial documents and of indirect indicators of climate, such as limnological indices (thickness and properties of annual sedimentary deposits), dendrologic indices (thickness and density of tree rings), palynological indices (composition of pollen in dated peat and other deposits), botanical indices (makeup and degree of decomposition of peat), glaciological indices (thickness and isotopic makeup of ice layers, positions of dated moraines) and the like. Our Institute's laboratory of climatology has run a joint quantitative interpretation of the ensemble of these data for the European part of the USSR. We found that the amplitude of the century-long and sub-century fluctuations in the seasonal mean and mean annual temperatures of the region was sometimes as high as 2°C, while the fluctuations in total annual precipitation were 20 percent.